Efficacy of oral appliance therapy in patients following uvulopalatopharyngoplasty failure - Stanley, Jeffrey J. (Laryngoscope Investig Otolaryngol, 2019)
OBJECTIVE: Uvulopalatopharyngoplasty (UPPP) is the most common surgical procedure performed to treat obstructive sleep apnea (OSA). This surgery, when performed alone, benefits only a minority of patients. This study was undertaken to determine the efficacy of oral appliance (OA) therapy following unsuccessful UPPP and assess for specific patient and polysomnographic characteristics that may identify those patients most likely to benefit from this combined treatment strategy. STUDY DESIGN: Retrospective of clinical outcomes in patients undergoing UPPP followed by treatment with an OA. METHODS: Polysomnographic results (baseline, status post‐UPPP, and status post‐UPPP with oral appliance use), age, gender, race, and body mass index were subjected to statistical analysis. RESULTS: The mean apnea hypopnea index (AHI) decreased from 23.6 at baseline to 8.6 following UPPP and oral appliance therapy. The mean O2 nadir increased from 83% at baseline to 89.9% following UPPP and treatment with an oral appliance. Fifty percent of patients (9/18) achieved an AHI <5 and were deemed “cured” of their disease. Seventy‐three percent of patients (13/18) achieved benefit with an AHI <20 and ≥50% reduction in their baseline AHI, deemed “successful therapy.” No statistically relevant demographic or polysomnographic differences were found between those who were “cured” and those with persistent disease with the exception that the O2 nadir status post UPPP was found to be lower in the “cured” group. CONCLUSION: Oral appliance therapy is an effective treatment option for the majority of patients who have persistent obstructive sleep apnea following unsuccessful UPPP. LEVEL OF EVIDENCE: 4